PERANCANGAN FASILITAS KAMPUNG WISATA DI SUNGAI JINGAH BANJARMASIN - Aini, Ahmad Qurrata; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Banjarmasin holds rich history and culture along its riversides which is supposedly to be conserved. Regarding this, the Department of Tourism of Banjarmasin City created a program Called Kota Pusaka and are willing to develop Sungai Jingah’s riverside settlement to become a Tourism Village. In this work of planning the writer applies Infill Design method to synthesize designs corresponding the surrounding houses, whether it would be matching or given the context of nowadays technology and materials. Infill Design also allows for contrasting designs to be formed. The purpose of applying Infill Design method is to add the functions of tourism into the existing settlement. The results are that the area able to be built on are empy sites and sites with broken down houses. The mass shapes for matching and compatible buildings and elements are gable roof or stepped-up roof. The mass shapes for contrasting buildings and elements are composed of transformed shapes with folds and rolls.